Human consumption of meat from roadkilled animals in the southwestern Amazon - Oliveira, Marcela Alvares; Pommer-Barbosa, Raul Afonso; Alves, Rômulo Romeu Nobrega; El Bizri, Hani Rocha; Messias, Mariluce Rezende; Doria, Carolina Rodrigues da Costa (Ethnobiology and Conservation, 2023)
The harvest of meat from wild animals is essential for the nutrition of many human populations in the Neotropics. Specific techniques are used to access wild meat, but collecting meat from road killed animals, or purposely run over animals to kill and consume the meat have not been documented so far. In this study we interviewed four residents of the state of Rondônia who claimed to consume roadkilled animals. Respondents cited only medium and large mammals (10 species in total) as the group from which wild meat is harvested, with one respondent claiming to intentionally run over the animals. The interviewees analyse the smell/putrefaction, swelling and exposure of viscera as criteria for not collecting the meat. The meat from roadkilled animals may pose a risk to the health of humans who consume it due to the foodborne diseases it may spread after the decomposition process. In addition, the practice of running over animals for consumption of their meat can cause potential impacts to the fauna and humans since it can reduce animal numbers and also cause serious accidents. Further investigations are needed to clarify whether this is widespread phenomenon occurring in other places of the Amazon and of the Neotropics.